Does L2 writing proficiency influence noun phrase complexity? A case analysis of argumentative essays written by Chinese students in a first-year composition course. (October 2019) - Lan, Ge; Lucas, Kyle; Sun, Yachao
Abstract: This corpus-based study investigated the association between noun phrase complexity and L2 writing proficiency based on the 11 noun modifiers in Biber, Gray, and Poonpon's (2011) index of complexity features. A corpus was built based on 100 argumentative papers written by first-year Chinese students, including 50 papers from high-proficiency students (TOEFL writing score > 23) and 50 papers from low-proficiency students (18 < TOEFL writing score < 23). The noun modifiers in Biber et al.'s (2011) index were then extracted with a computational program to calculate the frequencies of the noun modifiers. Via a Chi-square test on the normalized frequencies, the findings demonstrate an association (p = 0.016) between the 11 noun modifiers and the students' writing proficiency levels (i.e., high and low). Next, a residual analysis was applied, which pinpointed that four noun modifiers used by the students from both proficiency levels contribute to the association the most: attributive adjectives, relative clauses, premodifying nouns, and prepositional phrases (of). The four modifiers were then further explored and interpreted based on a qualitative analysis of the argumentative papers. Pedagogical implications are provided at the end to discuss possible ways of teaching the noun modifiers in an EAP writing course.